Unilateral gonadoblastoma with dysgerminoma in normal fertile woman having a child: Extremely rare occurrence with characteristic immunohistomorphology - Maithili Mandar Kulkarni; Siddhi Gaurish Sinai Khandeparkar; Avinash R Joshi; Pallavi V Bhayekar (Wolters Kluwer Medknow Publications, 2016)
Gonadoblastomas (GBYs) are rare gonadal tumors almost always arising from a dysgenetic gonad with a Y chromosome. Very rarely, GBYs appear in otherwise normal women with a history of pregnancy. The typical histological appearance of GBY can be altered by extensive deposition of basement membrane material, calcification, or overgrowth by a malignant tumor. Less than 10 cases have been reported with normal 46XX karyotype. Only six cases of GBY have been described in pregnant women. We present a unique case of GBY with dysgerminoma in a genotypically and phenotypically normal woman with a history of normal pregnancy, absence of virilization, and characteristic immunohistomorphological features.